Electrodeposition of multilayer Ni–W and Ni–W–alumina nanocomposite coatings. (4th May 2017) - Allahyarzadeh, M.; Aliofkhazraei, M.; Rouhaghdam, A. S.; Torabinejad, V.
Abstract : Multilayer Ni–W and Ni–W–Al2 O3 coatings with intermittent low and high concentrations of tungsten and alumina were electrodeposited through alternative variation of pulse parameters. Microstructural studies and elemental analyses of the coatings were carried out using scanning electron microscopy and energy dispersive X-ray spectroscopy, respectively. Profilometry and atomic force microscopy were employed to investigate the surface roughness at two different scales. Pin-on-disc wear test was used to evaluate the tribological properties. The corrosion resistance was also studied using potentiodynamic polarisation and electrochemical impedance spectroscopy methods. Results revealed that at lower duty cycles, more incorporation of alumina and more co-deposition of tungsten are achieved. Results indicated variable and alternative microhardness values corresponding to the different concentrations of tungsten and alumina in each specific layers. Wear tests demonstrated the descending trend of the wear rate as a function of sliding distance. It was found that alumina nanoparticles enhanced the corrosion resistance. GRAPHICAL ABSTRACT: